How can green differentiated capital requirements affect climate risks? A dynamic macrofinancial analysis - Yannis Dafermos; Maria Nikolaidi (Hans-Böckler-Stiftung, Macroeconomic Policy Institute (IMK), Forum for Macroeconomics and Macroeconomic Policies (FMM), 2021)
Using an ecological macrofinancial model, we explore the potential impact of the "green supporting factor" (GSF) and the "dirty penalising factor" (DPF) on climate-related financial risks. We identify the transmission channels by which these green differentiated capital requirements (GDCRs) can affect credit provision and loan spreads, and we analyse these channels within a dynamic framework in which climate and macrofinancial feedback effects play a key role. Our main findings are as follows. First, GDCRs can reduce the pace of global warming and decrease thereby the physical financial risks. This reduction is quantitatively small, but is enhanced when the GSF and the DPF are implemented simultaneously or in combination with green fiscal policies. Second, the DPF reduces banks' credit provision and leverage, making them less fragile. Third, both the DPF and the GSF generate some transition risks: the GSF increases bank leverage because it boosts green credit and the DPF increases loan defaults since it reduces economic activity. These effects are small in quantitative terms and are attenuated when there is a simultaneous implementation of the DPF and the GSF. Fourth, fiscal policies that boost green investment amplify the transition risks of the GSF and reduce the transition risks of the DPF; the combination of green fiscal policy with the DPF is thereby a potentially effective climate policy mix from a financial stability point of view.
Keywords: E12; E44; G18; Q54; 330; stock-flow consistent modelling; climate change; financial stability; green financialregulation